Phytochemical characterization and multi-biological potentials of Inula viscosa: new in vitro evidence - Celik Altunoglu, Yasemin; Ocal, Mustafa; Baloglu, Mehmet Cengiz; Aboujanah, Alsideeq Abdulsalam Ahmed; Horuz, Erdoğan; Llorent-Martínez, Eulogio J.; Uba, Abdullahi Ibrahim; Lazarova, Irina; Zengin, Gökhan; Güney, Kerim (Walter de Gruyter GmbH, 2025)
Abstract Inula viscosa is a common medicinal plant and is mostly spread in Mediterranean countries. The current study analyses I. viscosa extracts for antimicrobial capacity, phenolic content, antioxidant, enzyme inhibition, and molecular modeling. The extracts’ anticancer potential in prostate and breast cancer cells was evaluated, and their anti-metastatic and molecular activities were analyzed through gene expression. The most prevalent substances in the methanol extract of I. viscosa are phenolic acids, which include derivatives of caffeic acid and mono-, di-, and tri-caffeoylquinic acids. Dicaffeoylquinic acids represented 88 % of the quantified phenolics. The methanol extract showed a 50 % inhibitor concentration (IC50) of 101.4 μg/mL at 48 h in PC3 cells. Autophagy-related genes were found to be down-regulated in all three cancer cells. Regarding antimetastatic activity, the wound width remained ∼96 % at 48 h after ethyl acetate treatment in MCF-7 cells. The water extract had the highest total phenolic content and the strongest antioxidant capacity, followed by the methanol extract. Modest binding potential to B-cell leukemia-2 (Bcl-2) was observed with caffeoylquinic acid and caffeic acid derivatives, which may be related to pro-apoptotic/anticancer effects. Our results suggested that I. viscosa can be considered as an effective raw material for designing health-promoting applications.